Percursos no SUS: a Saúde Mental relacionada ao Trabalho a partir da Atenção Primária à Saúde - adriana de paula Rei (2016)
This dissertation analyses the journeys of four users of SUS [Brazilian Public Health System] in a city in Belo Horizonte (Minas Gerais) metropolitan area, whose complaints concerned mental health and work issues: a watchman sick after a robbery at his place of work, two sick maids, frequent users of care units and a plastic artist with a diagnosis of schizophrenia, who had in the work as an art educator a means of stabilization and health. The nature of this paper is exploratory, with methodology inspired in Louis Le Guillants (2006) pluridimensional approach and foundation on theoretical principles from Sociohistorical Psychology (Vigotski, 1999) and Concrete Psychology (Politzer, 1975). The users and the professionals stories on their experiences in SUS were presented in the study, with the examination of the communication among the various care units, particularly the relationship among the APS [Primary Health Care] team and the Centro de Referência em Saúde do Trabalhos (CEREST) [Workers Health Reference Center]. In order to do so, interviews with the users and health professionals were conducted, as well as group discussions of the cases with the teams and documental researches and analysis of information systems of SUS, of the Instituto Nacional do Seguro Social (INSS) [National Institute of Social Security] and of the existent supports to the development of Saúde do Trabalhador (ST) [Workers Health] interventions. The results of the research showed the importance of the elaboration of therapeutic and formative projects on health which cover interdisciplinary exchanges, alongside the users knowledges, practices and needs; of the recognition of work as a fundamental category to the understanding of the individuals biographies, life and health conditions; of the development of watchfulness over health and communication among the care units in the network; of the creation of vigilance on ST which grasp mental health issues and domestic workers; and of the development of actions in professional rehabilitation in SUS. Finally, one observed the analysis of professional practices in SUS and of the work of its users would allow the development of more effective actions for the sake of the advised integral attention to workers health and the improvement in the offer of sanitary services to the population.